Emerging trends: General fine-tuning (gft). (23rd July 2022) - Ward Church, Kenneth; Cai, Xingyu; Ying, Yibiao; Chen, Zeyu; Xun, Guangxu; Bian, Yuchen
Abstract: This paper describes gft (general fine-tuning), a little language for deep nets, introduced at an ACL-2022 tutorial. gft makes deep nets accessible to a broad audience including non-programmers. It is standard practice in many fields to use statistics packages such as R. One should not need to know how to program in order to fit a regression or classification model and to use the model to make predictions for novel inputs. With gft, fine-tuning and inference are similar to fit and predict in regression and classification. gft demystifies deep nets; no one would suggest that regression-like methods are "intelligent."